2021
DOI: 10.1002/acr2.11362
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Smoking and Primary Sjögren Syndrome Classification Using the Sjögren's International Collaborative Clinical Alliance Cohort

Abstract: Objective. The objective of this study was to examine the association of smoking with Primary Sjögren syndrome (pSS) classification and pSS diagnostic test results. We hypothesized that past and current smokers would have lower odds of being classified as having Sjögren syndrome (SS) and lower odds of having abnormal individual SS diagnostic test results compared with nonsmokers.Methods. Participants with suspected or established pSS were enrolled into the Sjögren's International Collaborative Clinical Allianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Patients with Sjögren's disease have also been reported to have more hypertension and type II diabetes which increase the risk for cardiovascular disease (32), but to smoke less because of symptoms of dry mouth (30). Multiple studies have demonstrated an inverse correlation of smoking and Sjögren's disease or for smoking and focal lymphocytic sialadenitis (33)(34)(35)(36)(37)(38)(39)(40), but differences between sex have not been reported. In this study a higher percentage of men with Sjögren's disease were smokers than women (49% men vs. 32% women), although the number of patients with data on smoking is relatively low (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Sjögren's disease have also been reported to have more hypertension and type II diabetes which increase the risk for cardiovascular disease (32), but to smoke less because of symptoms of dry mouth (30). Multiple studies have demonstrated an inverse correlation of smoking and Sjögren's disease or for smoking and focal lymphocytic sialadenitis (33)(34)(35)(36)(37)(38)(39)(40), but differences between sex have not been reported. In this study a higher percentage of men with Sjögren's disease were smokers than women (49% men vs. 32% women), although the number of patients with data on smoking is relatively low (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding other environmental factors implicated in autoimmunity, smoking is an established risk factor for seropositive RA 120 . By contrast, smoking is not thought to increase the risk of pSS development [121][122][123][124] . Instead, in the years preceding a diagnosis, individuals who later develop pSS are more prone to stop smoking than the general population 121 , and no discernible interactions have been detected between smoking and risk-related HLA alleles 121 .…”
Section: Environmental Factorsmentioning
confidence: 99%